Proposing the Introduction of Personalised Learning and Differentiated Learning into Saudi Arabian Education - Al-Omari, Saad bin Othman Mohammed; Keefe, Mary; Alterator, Scott (Journal of Educational and Psychological Sciences, 2021)
Personalised learning and the differentiated curriculum are ideal strategies to explore the needs of students and take full advantage of students’ abilities so they can achieve better outcomes in the learning process. This study focuses on the differentiated curriculum and explores its suitability for Saudi Arabia considering the country’s current education policies and vision. The study consists of three stages: reviewing the global personalised learning and differentiation literature, investigating the current education policies in Saudi Arabia, and reviewing the available differentiation literature conducted in Saudi Arabia. The findings suggest that despite the obstacles found in the application including low family participation and resistance from teachers this teaching strategy is suitable for Saudi Arabia. The Saudi vision for education and the country’s current policies do not conflict with the principles of differentiation, although success may require patience and building teacher capacity. With only a limited number of studies about differentiation in Saudi Arabia, more research about the impact of school management on the implementation of the differentiated curriculum is necessary.